The Revised Body Awareness Rating Questionnaire: Development Into a Unidimensional Scale Using Rasch Analysis. Issue 2 (31st October 2017) - Dragesund, Tove; Strand, Liv Inger; Grotle, Margreth
Abstract: Background: The Body Awareness Rating Questionnaire (BARQ) is a self-report questionnaire aimed at capturing how people with long-lasting musculoskeletal pain reflect on their own body awareness. Methods based on classical test theory were applied to the development of the instrument and resulted in 4 subscales. However, the scales were not correlated, and construct validity might be questioned. Objective: The primary purpose of this study was to explore the possibility of developing a unidimensional scale from items initially collected for the BARQ using Rasch analysis. A secondary purpose was to investigate the test-retest reliability of a revised version of the BARQ. Design: This was a methodological study. Methods: Rasch and reliability analyses were performed for 3 samples of participants with long-lasting musculoskeletal pain. The first Rasch analysis was carried out on 66 items generated for the original BARQ and scored by 300 participants. The items supported by the first analysis were scored by a new group of 127 participants and analyzed in a second Rasch analysis. For the test-retest reliability analysis, 48 participants scored the revised BARQ items twice within 1 week. Results: The 2-step Rasch analysis resulted in a unidimensional 12-item revised version of the BARQ with a 4-point response scale (scores from 0 to 36). It showed a good fit to the Rasch model, with acceptable internal consistency, satisfactory fit residuals, and no disordered thresholds. Test-retest reliability was high, with an intraclass correlation coefficient of .83 (95% CI = .71–.89) and a smallest detectable change of 6.3 points. Limitations: The small sample size in the second Rasch analysis was a study limitation. Conclusions: The revised BARQ is a unidimensional and feasible measurement of body awareness, recommended for use in the context of body-mind physical therapy approaches for musculoskeletal conditions.